COVID-19-related school closures and mathematical performance—findings from a study with grade 3 students in Germany - Gasteiger, Hedwig; Sachse, Karoline A.; Schumann, Kristoph; Gerve, Mona; Schulz, Axel; Engelbert-Kocher, Maria (Frontiers in Education, 2023)
Due to the COVID-19 pandemic, measures were taken that had a considerable impact on the situation in schools. In Germany, these measures lasted more than a year and ranged from school closures and distance learning to alternating teaching phases with small groups. In the present study, we examined whether third-grade students' mathematics performance changed in different content domains before and after the COVID-19-related changes in school. In a repeated cross-sectional design, we compared two cohorts of third graders (2019: N=1,905; 2021: N=3,203) based on standardized mathematics tests, constructed according to the German National Educational Standards, which allowed for a differential competence diagnostic for five content domains. There was a significant drop in performance overall. Generalized linear mixed models were used to model item and person properties and assess their effects on performance. For example, while the drop in the content domain Numbers & Operations was smaller than the overall drop in performance, the content domains Space & Shape and Data, Frequency, Probability were more affected. The findings of this study may be explained by the results of numerous surveys of students, teachers and parents, which indicated that a lot of time was spent on exercises and reproduction tasks during distance learning.